2021
DOI: 10.3390/ijms222313064
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in Cystic Fibrosis Therapies: Targeting SLC26A9

Abstract: SLC26A9, a constitutively active Cl− transporter, has gained interest over the past years as a relevant disease modifier in several respiratory disorders including Cystic Fibrosis (CF), asthma, and non-CF bronchiectasis. SLC26A9 contributes to epithelial Cl− secretion, thus preventing mucus obstruction under inflammatory conditions. Additionally, SLC26A9 was identified as a CF gene modifier, and its polymorphisms were shown to correlate with the response to drugs modulating CFTR, the defective protein in CF. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…We speculate that the airway epithelium in these rare lung sections was not fully differentiated, possibly due to inflammation. Importantly, SLC26A9 was only found in ciliated epithelial cells, which corresponds well to the interaction of SLC26A9 and other SLC26A solute transporters with CFTR, as described in several previous reports [ 9 , 14 , 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…We speculate that the airway epithelium in these rare lung sections was not fully differentiated, possibly due to inflammation. Importantly, SLC26A9 was only found in ciliated epithelial cells, which corresponds well to the interaction of SLC26A9 and other SLC26A solute transporters with CFTR, as described in several previous reports [ 9 , 14 , 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…Besides different studies seem to indicate a relevant role of this protein in the gastrointestinal tract, the contribution of SLC26A9 to the lung function is still elusive, highlighting the need for further investigations. For example, despite a few studies reporting some SLC26A9 expression in human bronchial airways [18,24], others have failed to find relevant expression or detected SLC26A9 only in a small fraction of The cartoon shows a simplified airway epithelial cell model with some of the various transporters, channels, and exchangers involved in ion secretion mechanisms. Among these, SLC26A9 could be potentially targeted to circumvent the reduced chloride secretion due to the loss of function of CFTR by searching for small molecules acting as activators or potentiators of its ion transport activity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these findings, not much more effort has been made in the characterization of SLC26A9 protein expression in human airway tissue, until the very recent work by Pinto and colleagues [ 24 ]. These authors found some SLC26A9-positive signals by immunofluorescence on native human bronchial tissues (by using a commercially available antibody, NBP2-30425) [ 24 ].…”
Section: Slc26a9 Tissue Cellular and Subcellular Localizationmentioning
confidence: 99%
See 2 more Smart Citations